Impedance Measurements using Genetic Algorithms and Multiharmonic Signals - Janeiro, Fernando M. (2010)
In this paper, a procedure to measure impedances using data-acquisition boards and genetic algorithms is developed. This approach to impedance measurements has the advantage of being low cost. The multiharmonic acquired waveforms are characterized using a genetic algorithm that finds the frequency of the signal, which, in turn, is used in a multiple linear least-squares (LS) waveform-fitting algorithmd. The magnitude and phase of the unknown impedance can then be evaluated. A multiharmonic signal is used so that the frequency dependence of the impedance can be obtained from a single measurement. The measurement results are validated by measurements made with an impedance analyzer. The main advantage of the genetic algorithm over traditional search methods is its robustness to convergence problems.